2019
DOI: 10.1016/j.pedhc.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-Informed Care: Essential Elements for Pediatric Health Care

Abstract: Childhood psychosocial trauma exposure is highly prevalent and associated with risk for poor physical and mental health outcomes extending throughout life. In a study of nearly 54,000 adult Americans (Gilbert et al., 2015), 60% reported experiencing at least one adverse childhood experience (ACE). According to the National Survey of Child Health, 48% of American children have suffered at least one ACE (Bethell, Newacheck, Hawkes, & Halfon, 2014). The U.S. Department of Health and Human Services (2017) states t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 41 publications
(43 reference statements)
2
27
0
Order By: Relevance
“…DBT has an extensive research base supporting its use and a history of adapting programmes to different groups. DBT skills groups in particular have been adapted as standalone interventions as part of stepped care models (Babeva et al, 2020) and is considered a 'trauma informed' approach to care for adolescents and young people (Hornor et al, 2019). However, there is an urgent need for research exploring adapting existing programmes to online deliver, particularly for those with the highest level of need.…”
Section: Discussionmentioning
confidence: 99%
“…DBT has an extensive research base supporting its use and a history of adapting programmes to different groups. DBT skills groups in particular have been adapted as standalone interventions as part of stepped care models (Babeva et al, 2020) and is considered a 'trauma informed' approach to care for adolescents and young people (Hornor et al, 2019). However, there is an urgent need for research exploring adapting existing programmes to online deliver, particularly for those with the highest level of need.…”
Section: Discussionmentioning
confidence: 99%
“…22,41 Core features of trauma-informed systems include the integration of trauma-informed concepts and principles into policies, procedures, and practices, and building awareness, recognition, and implementation of screening, assessment and treatment services for trauma. [42][43][44][45] Thus, to provide TIC, there must be a commitment to these tasks throughout the organization with a resultant paradigm shift. 46,47 This shift, then, facilitates the identification of trauma and creates pathways to holistic family well-being assessment and intervention, the prevention of long-term negative health outcomes and a reduction in healthcare costs.…”
Section: What Is Trauma-informed Care?mentioning
confidence: 99%
“…46,47 This shift, then, facilitates the identification of trauma and creates pathways to holistic family well-being assessment and intervention, the prevention of long-term negative health outcomes and a reduction in healthcare costs. 29,[42][43][44]46,48,49 TIC can also benefit medical professionals with a personal history of trauma or who have experienced work-related trauma. 50,51 Trauma-informed organizations that use trauma-sensitive practices can decrease traumarelated triggers and improve staff health, resiliency, and efficiency while enhancing the quality of care for patients and families.…”
Section: What Is Trauma-informed Care?mentioning
confidence: 99%
“…Hornor et al (2018) also found a universal definition of TIC across the literature as difficult with variation in conceptualization depending on the organization and discipline. However, reference to the aforementioned four-Rs in terms of trauma-awareness (realize), trauma-focused evidence-based practice (recognition), use of standardized screening measures (responding), and organizational implementation related to collaboration, service coordination, safe physical environments, written policies, and defined leadership (resist re-traumatization) are reviewed and identified as best practices for trauma-informed care in pediatric health (Goddard, 2021;Hanson & Lang, 2016;Hornor et al, 2018).…”
Section: Trauma-informed Carementioning
confidence: 99%
“…An abundant amount of the literature reviewed refers back to SAMHSA's six key principles of trauma-informed approaches which are based around: (a) safety (both physical and psychological); (b) trustworthiness and transparency (where transparent decisions build and maintain trust); (c) peer support (including those who have experienced traumatic events); (d) collaboration and mutuality (across all relationships, with meaningful sharing of decision making and power); (e) empowerment, voice, and choice (eliminating power differentials and promoting self-advocacy skills); and (f) cultural, historical, gender issues (rejecting stereotypes and biases with leverage access to connections needed) (Chafouleas et al, 2016). Hornor et al (2018) also found a universal definition of TIC across the literature as difficult with variation in conceptualization depending on the organization and discipline. However, reference to the aforementioned four-Rs in terms of trauma-awareness (realize), trauma-focused evidence-based practice (recognition), use of standardized screening measures (responding), and organizational implementation related to collaboration, service coordination, safe physical environments, written policies, and defined leadership (resist re-traumatization) are reviewed and identified as best practices for trauma-informed care in pediatric health (Goddard, 2021;Hanson & Lang, 2016;Hornor et al, 2018).…”
Section: Trauma-informed Carementioning
confidence: 99%